KERAUHAN: Antara Pertunjukan Seni Sacral Dan Profan (Kajian Teologi Hindu) - Susi Susi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Trance becomes very trending discussed in the order of life of the local community, because trance can not only occur a series of the implementation of yajna ceremony but can happen because there is an energy intervention outside human reason to show its existence. Kerauhan by balinese is very common in the implementation of yajna ceremony, lately it is often debated between profanity and kerauhan that actually occurs / sacral. It is important to review this in order to correct the relevant information. Through qualitative approach is expected to find relevant research results to be applied in people's social life.Kerauhan can be classified in various forms such as a gluttony with the form of a god, of course the gluttony in this form will act calmly, tending to give advice in the implementation of yajna ceremony; kerauhan in the form of pepatih reflects how there is a kingdom of gods complete with pepatih, so that when there is a gluttony one will act like a royal patih; the apeuhan in the form of a sacred animal, certainly in the form of this kind of filth one will act like an animal; bhuta kerauhan ngunying (stabbing kris into him) bergitu also with other forms of kerauhan.